Establishment of mouse lung tumor models and development of new therapeutic approaches - Savai, Rajkumar; Justus Liebig University Giessen (My University, 2005)
Two mouse models of lung cancer were used to investigate cancer progression, cancer treatment, and cancer imaging. One model was established by subcutaneous injection of human adenocarcinoma A549 cells and lewis lung carcinoma (LLC1) cells, the other by intratracheal instillation of LLC1 cells. In the first study, the role of HIF-1 in tumor progression was investigated. Overexpression of HIF-1alpha by genetic alteration of adenocarcinoma cells decreased tumor size, due to decreased proliferation and increased apoptosis, despite an augmented vascularization observed in these tumors. In a further study, tumor regression by immunological approaches was attempted. Hybrids were generated by fusing dendritic cells and syngeneic poorly immunogenic LLC1 cells of C57/BL6 origin. Hybrid immunization induced the expression of a variety of cytokines and the partial host protective immunity against LLC1 tumor challenge. Moreover, hybrid vaccination and adoptive immunotherapy resulted in notable tumor regression. For establishing small animal tumor imaging in our study, three different imaging modalities, micro computed tomography (müCT), multi slice computed tomography (MSCT), and flat panel volumetric computed tomography (fpvCT) were investigated. The müCT images of intrapulmonary tumors suggested that µCT is a reliable and non-destructive method for quantifying the volume of intrapulmonary tumors in the mouse model. In addition, müCT can be used to evaluate tumor angiogenesis. We exploited MSCT and fpvCT for the in vivo imaging and detection of lung nodules in a mouse LLC1 lung tumor model. FpvCT allowed easy monitoring of a lung tumor model with high resolution, facilitating follow-up investigations in cancer research. In addition, the superiority of fpvCT over MSCT was clearly demonstrated. Furthermore, both imaging modalities (müCT and fpvCT), along with fluorescent microspheres, were applied to delineate the relative contribution of blood supply via the pulmonary and the systemic arteries to LLC1 lung tumors. All three methods revealed the pulmonary artery to be the primary functional source for feeding vessels to the lung tumors. Moreover, both modalities demonstrated the microanatomy of the vessels and blood-supplying tissue. The development of experimental mouse lung tumor models is essential to the understanding of tumor pathophysiology and vascular microanatomy. Our findings can be used to identify novel targets for anticancer treatment and for site specific drug targeting. Additionally, the successful employment of various computed tomography systems for lung cancer imaging in rodents offers in vivo evaluation of such strategies.

Zur Untersuchung von Tumorwachstum, Tumortherapie und Tumordarstellung wurden zwei verschiedene Lungentumor-Mausmodelle etabliert. Das eine Modell wurde durch die subkutane Injektion von menschlichen Adenokarzinom A549 Zellen oder Lewis-lung-karzinom zellen (LLC1), das andere durch die intratracheale Verabreichung von LLC1 Zellen ausgelöst. In der ersten Studie wurde die Rolle von HIF-1 auf das Tumorwachstum analysiert. Die genetisch verursachte Überexpression von HIF-1alpha in Adenokarzinom-Zellen führte, trotz erhöhter Gefäßbildung in den untersuchten Tumoren, über eine verminderte Proliferation und gesteigerte Apoptose zu einer Verminderung des Tumorwachstums. Eine weitere Untersuchung beschäftigte sich mit einem immunologischen Ansatz der Tumortherapie. Es wurden dendritische Zellen und syngene, schwach immunogene LLC1 Zellen, abgeleitet von C57/BL6 Mäusen, fusioniert. Immunisierung mit diesen Zellhybriden induzierte die Expression verschiedener Zytokine. Desweiteren wurde eine effektive Immunantwort gegen schwach immunogene Tumorzellen und eine gesteigerte T-lymphozytär vermittelte Zerstörung der Tumorzellen beobachtet. Dieser Effekt ließ sich sowohl durch Zellhybrid-Vakzinierung als auch durch die Übertragung von zuvor Zell hybrid-aktivierten T-Lymphozyten herbeiführen. Zur Darstellung der induzierten Maus-Tumore wurden die Methoden der Mikro-Computertomographie (müCT), der Mehrschicht- Computertomographie (MSCT) und der Flachwandvolumen- Computertomographie (fpvCT) angewendet. Die mü;CT Darstellung von intrapulmonalen Tumoren erwies sich als eine geeignete, nicht-destruktive Methode für die Quantifizierung des Tumorvolumens. Außerdem war es mit müCT möglich, die Gefäßversorgung der Tumore darzustellen. Weiterhin haben wir die in vivo Darstellung und Detektion von Lungentumorknoten im LLC1-Lungen Modell mittels MSCT und fpvCT, untersucht. Aufgrund der präzisen Bestimmung der Tumorgröße ermöglicht die fpvCT die Analyse der Tumorprogression in zeitlicher Abfolge. Zusätzlich konnte eine Überlegenheit der fpvCT gegenüber der MSCT nachgewiesen werden. In Ergänzung wurden die Methoden der müCT und fpvCT zur Detektion von Fluoreszenzmikropartikeln für die Differenzierung von pulmonalarteriellen und systemarteriellen Blutflusses hinsichtlich der Versorgung des Tumorgewebes eingesetzt. Der strenge Hinweis, dass die Pulmonalarterien als funktionelle Quelle der Lungentumorgefäßversorgung dienten, konnte von allen drei eingesetzten Methoden erbracht werden. Darüber hinaus war es möglich, die Mikroanatomie der Gefäße sowie blutversorgende Gewebsbrücken darzustellen.
Erstelleng von Lungen-Tumor-Modellen bei Mäusen und Entwicklung von neuen therapeutischen Vorgehensweisen
Keywords: ddc:610